Experimental and calculation determination of the mechanical properties of the material of GTE blades - Михаил Романович Ткач (National Aerospace University «Kharkiv Aviation Institute», 2021)
A schematic description of a stand based on a digital speckle interferometer with a diffuse reference wave is given, which makes it possible to determine the natural frequencies and vibration modes of the blades in real-time. In the frequency range of 100 ... 3000 Hz, an experimental study of the vibration characteristics of a turbine rotor blade of a gas turbine engine was carried out, under free boundary conditions, which were achieved by placing the blade on soft silicone racks. Blade dimensions: height along the trailing edge - 288 mm, a chord in the middle section - 88.5 mm. 7 modes of vibrations have been identified. The technology of creating a solid-state geometric model of a rotor blade based on a faceted body obtained by 3D scanning with an accuracy of 0.01 mm is presented. The finite element method, using the Lagrange variation principle, is used to calculate the values of natural frequencies and vibration modes of a blade based on the developed geometric model. Concerning the frequency range 100 ... 3000 Hz, using the Ansys Workbench software package, a series of calculations of the resonant frequencies of the blade, by the finite element method, in the range of variation of the values of mechanical properties was carried out: Young's modulus E = 200 ... 230 GPa; Poisson's ratio μ = 0.26 ... 0.3. The density of the material: ρ = 7830 kg / m³, determined experimentally, by the method of hydrostatic weighing. The final element used in the calculation is (tetrahedron) SOLID 187; the minimum element size is 0.6 mm. The total number of elements is about 1.5 ∙ 10⁶. Based on the two-dimensional spline interpolation of the calculated data, the dependence of the standard deviation of the calculated and experimental values on the adopted mechanical properties of the material of the rotor blade is built. In the range of values E = 215 ... 217 GPa and μ = 0.295 ... 0.3, the minimum standard deviation of the calculated frequencies from their experimental values is 0.73%. Provided the value of the standard deviation of frequencies is 1%, the range of values of mechanical properties will be: E = 211 ... 220 GPa and μ = 0.26 ... 0.3. It is shown that narrowing the studied range of values of Young's modulus and Poisson's ratio does not significantly affect the results obtained.